1997
DOI: 10.1007/bf02242457
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary therapies by individuals with ‘arthritis’

Abstract: The popularity of complementary medicine is at an all-time high. Rheumatological patients are amongst its most frequent users. This survey was aimed at generating insight into this phenomenon. A self-selected convenience sample of 3384 individuals with 'arthritis' was sent a purpose-designed questionnaire. 1020 completed questionnaires were received (response rate = 30.1%). One third of respondents had received at least one treatment from a complementary practitioner. Orthodox therapies were generally perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 6 publications
0
19
0
4
Order By: Relevance
“…Second, the MEPS measures only medical expenditures and does not capture services for which there is no exchange of money. Third, we did not include in this analysis expenditures for complementary and alternative medicine, which is becoming an increasingly common treatment modality, especially among individuals with AORC (50,51). Fourth, the data from the current study precede the introduction of biologics for the treatment of rheumatoid arthritis, more-aggressive testing for the presence and treatment of osteoporosis, and the growth of the coxibs and/or the use of protonpump inhibitors with traditional nonsteroidal antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the MEPS measures only medical expenditures and does not capture services for which there is no exchange of money. Third, we did not include in this analysis expenditures for complementary and alternative medicine, which is becoming an increasingly common treatment modality, especially among individuals with AORC (50,51). Fourth, the data from the current study precede the introduction of biologics for the treatment of rheumatoid arthritis, more-aggressive testing for the presence and treatment of osteoporosis, and the growth of the coxibs and/or the use of protonpump inhibitors with traditional nonsteroidal antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, given the persistent and chronic nature of the disease and the potential side effects associated with many pharmacologic approaches, persons with RA tend to be particularly high users of complementary and alternative medicine (CAM) therapies (8). For example, a recent survey (9) found that 46% of RA patients being seen in rheumatology clinics across the country reported using some form of CAM.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction with the therapeutic encounter was markedly greater with CAM practitioners than with GPs. 40 Again, satisfaction with the time spent on the patient was 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 To improve the current situation, we should consider ways of maximising the benefits of nonspecific therapeutic effects within the realm of mainstream medicine. A recent systematic review qualitatively synthesised the relevant evidence in relation to cancer care.…”
mentioning
confidence: 99%